Optical hydrogen absorption consistent with a bow shock around the hot Jupiter HD 189733 b. Issue Volume 11:Issue S320(2015) (9th September 2016) - Cauley, P. Wilson; Redfield, Seth; Jensen, Adam G.; Barman, Travis; Endl, Michael; Cochran, William D.
Abstract: Hot Jupiters, i.e., Jupiter-mass planets with orbital semi major axes of <10 stellar radii, can interact strongly with their host stars. If the planet is moving supersonically through the stellar wind, a bow shock will form ahead of the planet where the planetary magnetosphere slams into the the stellar wind or where the planetary outflow and stellar wind meet. Here we present high resolution spectra of the hydrogen Balmer lines for a single transit of the hot Jupiter HD 189733 b. Transmission spectra of the Balmer lines show strong absorption 70 minutes before the predicted optical transit, implying a significant column density of excited hydrogen orbiting ahead of the planet. We show that a simple geometric bow shock model is able to reproduce the important features of the absorption time series while simultaneously matching the line profile morphology. Our model suggests a large planetary magnetic field strength of 28 G. Follow-up observations are needed to confirm the pre-transit signal and investigate any variability in the measurement.